1995
DOI: 10.1248/bpb.18.1154
|View full text |Cite
|
Sign up to set email alerts
|

Application of Curdlan to Controlled Drug Delivery. III. Drug Release from Sustained Release Suppositories in Vitro.

Abstract: The use of curdlan, a natural beta-1,3-glucan, in the preparation of sustained release suppositories was studied in vitro. To prepare the suppositories, indomethacin, prednisolone or salbutamol sulfate was mixed with curdlan gel. Preparation conditions, including heating time and curdlan concentrations of 5 and 10%, had little effect on the drug release. The tonicity (hypotonic or isotonic) of the media for the suppository preparation and for in vitro drug release study also had little effect on drug release. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In recent years, this polysaccharide attracted growing attention in biomedical and pharmaceutical applications [20]. Encapsulation of theophylline, salbutamol sulfate, prednisolone, indomethacin, doxorubicin and epirubicin with β-glucan has been shown to improve the pharmacokinetics of drugs [21][22][23][24]. Moreover, numerous studies reveal positive effect of β-glucans and its derivatives on health, particularly in the field of immunology: they improve wound healing and show antioxidant, antiviral, antibacterial, anti-inflammatory and DNA-protecting activity [25][26][27][28].…”
mentioning
confidence: 99%
“…In recent years, this polysaccharide attracted growing attention in biomedical and pharmaceutical applications [20]. Encapsulation of theophylline, salbutamol sulfate, prednisolone, indomethacin, doxorubicin and epirubicin with β-glucan has been shown to improve the pharmacokinetics of drugs [21][22][23][24]. Moreover, numerous studies reveal positive effect of β-glucans and its derivatives on health, particularly in the field of immunology: they improve wound healing and show antioxidant, antiviral, antibacterial, anti-inflammatory and DNA-protecting activity [25][26][27][28].…”
mentioning
confidence: 99%
“…The gels are prepared by mixing curdlan in drug solutions at 5-10% curdlan concentration, adding the suspension to a glass test tube, heating the test tube in water bath at the desired temperature for 10 minutes and then unmolding the gel. The experiments conducted in [32] have demonstrated that a high-set gel can lower the rate of drug release. The curdlan based gels have been able to provide a sustained release of drugs for compared to commercially available formulations.…”
Section: Encapsulation Within Gelsmentioning
confidence: 99%
“…The curdlan based gels have been able to provide a sustained release of drugs for compared to commercially available formulations. These gels can be used as drug delivery suppositories for rectal administration, which bypasses hepatic first pass clearance [32].…”
Section: Encapsulation Within Gelsmentioning
confidence: 99%
“…Drug release increases inversely with the melting temperatures of suppositories [17,166]. Lecithin (curdlan) hardens the suppository, which delays suppository melt and prolongs drug release [80]. Large drug particle sizes delay absorption [29,42,147,184], though this has been disputed [102].…”
Section: Pharmaceutical Characteristicsmentioning
confidence: 99%